Direct projections from hypothalamic orexin neurons to brainstem cardiac vagal neurons. (17th December 2016) - Dergacheva, Olga; Yamanaka, Akihiro; Schwartz, Alan R.; Polotsky, Vsevolod Y.; Mendelowitz, David
Highlights: Photoactivation of orexin neurons by channelrhodopsin-2 expression. Orexin neurons monosynaptically project to brainstem cardiac vagal neurons. Orexin cells release GABA and glutamate to modulate cardiac vagal neuron activity. Abstract: Orexin neurons are known to augment the sympathetic control of cardiovascular function, however the role of orexin neurons in parasympathetic cardiac regulation remains unclear. To test the hypothesis that orexin neurons contribute to parasympathetic control we selectively expressed channelrhodopsin-2 (ChR2) in orexin neurons in orexin-Cre transgenic rats and examined postsynaptic currents in cardiac vagal neurons (CVNs) in the dorsal motor nucleus of the vagus (DMV). Simultaneous photostimulation and recording in ChR2-expressing orexin neurons in the lateral hypothalamus resulted in reliable action potential firing as well as large whole-cell currents suggesting a strong expression of ChR2 and reliable optogenetic excitation. Photostimulation of ChR2-expressing fibers in the DMV elicited short-latency (ranging from 3.2 ms to 8.5 ms) postsynaptic currents in 16 out of 44 CVNs tested. These responses were heterogeneous and included excitatory glutamatergic (63%) and inhibitory GABAergic (37%) postsynaptic currents. The results from this study suggest different sub-population of orexin neurons may exert diverse influences on brainstem CVNs and therefore may play distinct functional roles in parasympathetic control of the heart.